2018
DOI: 10.1080/0284186x.2018.1505053
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive radiotherapy for head and neck cancer

Abstract: Introduction: Large anatomical variations can be observed during the treatment course intensitymodulated radiotherapy (IMRT) for head and neck cancer (HNC), leading to potential dose variations. Adaptive radiotherapy (ART) uses one or several replanning sessions to correct these variations and thus optimize the delivered dose distribution to the daily anatomy of the patient. This review, which is focused on ART in the HNC, aims to identify the various strategies of ART and to estimate the dosimetric and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 76 publications
1
89
0
1
Order By: Relevance
“…Different studies have reported on anatomical and dosimetric changes in HNC in which the parotid gland as the most reviewed organ at risk [18]. In a review article of Castelli et al they stated that ART may decrease toxicity and improve local control for locally advanced HNC [19]. However, appropriate selection of patients in which the gain of ART outweighs the effort is challenging [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have reported on anatomical and dosimetric changes in HNC in which the parotid gland as the most reviewed organ at risk [18]. In a review article of Castelli et al they stated that ART may decrease toxicity and improve local control for locally advanced HNC [19]. However, appropriate selection of patients in which the gain of ART outweighs the effort is challenging [19].…”
Section: Discussionmentioning
confidence: 99%
“…In a review article of Castelli et al they stated that ART may decrease toxicity and improve local control for locally advanced HNC [19]. However, appropriate selection of patients in which the gain of ART outweighs the effort is challenging [19]. More insight can be expected from ongoing clinical trials, such as the Artforce trial (ClinicalTrials.gov Identifier: NCT01504815) and the Admire trial (ClinicalTrials.gov Identifier: NCT03376386) or dose accumulation strategies to guide patient selection in order to reduce the amount of re-planning in HNC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The process not only is tedious but also suffers from substantial intra‐ and interobserver variabilities . The time‐consuming process is further challenged by the need to adapt H&N treatment plans due to the interfractional changes commonly occur to these patients . The anatomical changes can be observed in daily cone beam CT (CBCT) images for patient positioning, but better quality fan beam simulation CTs are commonly acquired to more accurately assess the anatomical changes, delineate the OARs, and perform dose calculation in off‐line adaptive radiotherapy planning.…”
Section: Introductionmentioning
confidence: 99%
“…3 The time-consuming process is further challenged by the need to adapt H&N treatment plans due to the interfractional changes commonly occur to these patients. 4 The anatomical changes can be observed in daily cone beam CT (CBCT) images for patient positioning, but better quality fan beam simulation CTs are commonly acquired to more accurately assess the anatomical changes, delineate the OARs, and perform dose calculation in off-line adaptive radiotherapy planning. Recent advances in MRguided radiotherapy (MRgRT) provide H&N images with superior soft tissue contrast on the daily basis, 5 further paving the path to online adaptive radiotherapy, where automated segmentation of the OARs is more urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Which patients would benefit from ART in head and neck cancer? What is the optimal timing? Should it be performed every five fractions, within the first 10 fractions? There are no randomized studies that show clinical benefit. How should treatment be altered when changes are detected?…”
Section: Opening Statementsmentioning
confidence: 99%